Graham/Hijmans/Kamp/Watkins Family Reunion at Lake Nacimiento - Watkins, Howard::::::::: (1989)
Group photo: 1st row: Howard Watkins, Robin Watkins, Peter Graham, Jesse Graham, Carey Hijmans, Cody Iyall and Adam Watkins: 2nd row: Richard Graham, Christine Watkins; Jackie Hijmans holding Jamie Hijmans, Marty Hijmans, Jerry Kamp, Frances Kamp, Gail Graham, Greg Graham and Teresa Graham holding Stanley Graham